Metastasectomy for metachronous pulmonary and hepatic metastases from nasopharyngeal carcinoma: Report of 6 cases and review of the literature. Issue 2 (15th July 2015) - Lim, Samuel Jun Ming; Iyer, Narayanan Gopalakrishna; Ooi, London Lucien; Koong, Heng Nung; Chung, Alexander Yaw Fui; Tan, Hiang Khoon; Soo, Khee Chee; Tan, Ngian Chye
ABSTRACT: Background: Metastatic nasopharyngeal carcinoma (NPC) is commonly treated with palliative chemotherapy. The purpose of this study was to review the feasibility of metastasectomy for metachronous pulmonary and hepatic metastases from NPC. Methods: We present 6 patients who developed metachronous metastases from NPC (4 patients with pulmonary metastases and 2 patients with hepatic metastases) and underwent curative resection. Results: Four patients are still alive with no recurrence of NPC after metastasectomy. Two patients died with postoperative survival periods of 57 and 70 months and recurrence‐free intervals of 14 and 39 months, respectively. Conclusion: Metastasectomy is a feasible option for the treatment of metachronous and resectable oligometastatic NPC to the lung and liver. Application of appropriate selection criteria would be required. © 2015 Wiley Periodicals, Inc. Head Neck 38: E37–E40, 2016